ALSUntangled #60: light therapy. Issue 3 (3rd April 2022) - Bedlack, Richard; Barkhaus, Paul; Barnes, Ben; Bereman, Michael; Bertorini, Tulio; Carter, Gregory; Crayle, Jesse; Kihuwa-Mani, Sky; Bowser, Robert; Kittrell, Pamela; McDermott, Christopher; Pattee, Gary; et al.
Abstract: ALSUntangled reviews alternative and off-label treatments for people with ALS. Here we review light therapy. We show that it has theoretically plausible mechanisms, three flawed pre-clinical data, studies, and one incompletely documented case report supporting its use. We explain why further studies are needed to determine whether any specific light therapy protocol can help people with ALS.